LAPORAN KASUS: MORBUS HANSEN TIPE MULTIBASILER - Rafilah Dinira; Hapsari Triandriyani; Hadi Firmansyah (Cahaya Ilmu Bangsa Institute, 2024)
ABSTRACT Background: Morbus Hansen is a chronic infectious disease caused by Mycobacterium leprae. This disease can cause serious complications if left untreated, especially the multibacillary (MB) type, which is characterized by numerous skin lesions and significant nerve damage. Objective: This case report aims to provide a diagnostic description and management of multibacillary type Morbus Hansen patients. Method: The case of a 60 year old male patient was reported with complaints of non-itchy red spots and numbness in the hands. Dermatological and bacteriological examinations are performed to confirm the diagnosis. Results: The diagnosis of multibacillary type Hansen's Morbus was confirmed based on the presence of more than five lesions, loss of sensation, and positive results of the acid-fast bacillus (BTA) examination. Treatment was given in the form of Multi-Drug Treatment (MDT) with Rifampicin, Dapsone and Clofazimine according to WHO recommendations. Conclusion: Early treatment of multibacillary Morbus Hansen cases can prevent further complications. Education regarding the importance of appropriate treatment and reducing stigma is also very important to improve patient quality of life ABSTRAK Latar Belakang: Morbus Hansen merupakan penyakit infeksi kronis yang disebabkan oleh Mycobacterium leprae. Penyakit ini dapat menimbulkan komplikasi serius jika tidak ditangani, terutama pada tipe multibasiler (MB), yang ditandai dengan banyaknya lesi kulit dan kerusakan saraf yang signifikan. Tujuan: Laporan kasus ini bertujuan untuk memberikan gambaran diagnostik dan penatalaksanaan pada pasien Morbus Hansen tipe multibasiler. Metode: Dilaporkan kasus seorang pasien laki-laki berusia 60 tahun dengan keluhan bercak kemerahan yang tidak gatal serta mati rasa pada tangan. Pemeriksaan dermatologi dan bakteriologis dilakukan untuk memastikan diagnosis. Hasil: Diagnosis Morbus Hansen tipe multibasiler ditegakkan berdasarkan adanya lebih dari lima lesi, hilangnya sensasi, dan hasil positif pemeriksaan basil tahan asam (BTA). Pengobatan diberikan berupa Multi-Drug Treatment (MDT) dengan Rifampisin, Dapson, dan Clofazimine sesuai rekomendasi WHO. Kesimpulan: Penanganan dini pada kasus Morbus Hansen tipe multibasiler dapat mencegah komplikasi lebih lanjut. Edukasi mengenai pentingnya pengobatan yang tepat dan pengurangan stigma juga sangat penting untuk meningkatkan kualitas hidup pasien.